Treatment of unruptured middle cerebral artery aneurysms: Systematic review in an attempt to perform a network meta-analysis - Arrese, Ignacio; García-García, Sergio; Cepeda, Santiago; Sarabia, Rosario (Frontiers in Surgery, 2022)
OBJECTIVE Open surgical clipping has been generally considered the best treatment option for unruptured middle cerebral artery aneurysms (uMCAAs). However, this type of aneurysm is being treated endovascularly with the appearance of new devices. We have carried out a systematic review of randomized and quasi-experimental studies to conduct a network meta-analysis (NMA) to assess the safety and efficacy of the different treatment methods currently used in uMCAAs. METHODS The literature was searched by using PubMed, and Google Scholar databases. Eligibility criteria were: randomized or quasi-experimental studies including at least 5 cases per arm and reporting duration of follow-up and number of lost cases. The end points were: angiographic success, final neurological outcome and need of retreatments. RESULTS We could only analyze 4 quasi-experimental studies with 398 uMMAAs. All of them compared clipping vs coiling. Clipping showed better results than Coiling in all analyzed end points. We could not conduct the proposed NMA because of the absence of randomized or quasi-experimental studies. Instead, a systematic review is further discussed. CONCLUSIONS There is an urgent need for comparative studies on the treatment of uMCAAs